Deposition of PTFE thin films by RF plasma sputtering on < 100 > silicon substrates - Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Polymers have been studied extensively due to the wonderful array of properties presented by them. Polymer materials can be coated/deposited by various techniques like sputtering (magnetron, ion beam, RF or dc), plasma polymerization, etc. and can be used in coatings, paint industries, etc. The present study deals with the RF sputter deposition of poly(tetrafluoro ethylene) (PTFE), commonly known as Teflon. Depositions were carried out on mirror polished silicon (1 0 0) substrates at different powers in the range of 100-200 W. The deposition time was kept constant at 60 min. The sputtered film shows lower contact angle of 50&DEG; with water and 44&DEG; with diiodomethane, a lower interfacial tension value of 0.76 dyne/cm, indicating hydrophilicity and good adhesion of the film with the substrate. FHR indicates presence of C-F, C-F-2 bonding groups in the deposited film. Further, XPS study shows presence of CF3 (292.2 eV), CF2 (290.8 eV), C-F (288.0 eV) and C-CF (286.4 eV) moieties indicating deposition of PTFE films at higher power levels of plasma. © 2004 Elsevier B.V. All rights reserved.
Keywords: Contact angle measurement; FTIR; PTFE; RF plasma sputtering; XPS